Comprehensive review of vibration-assisted welding processes: Mechanisms, applications, and future directions - Ranjan, Rajeev; Cep, Robert; Kumar, Ashwini; Srivastava, Mayank; Altarazi, Faisal; Dogra, Namrata; Kumar, Ajay; Chand, Subhash; Samal, S. P. (Frontiers in Mechanical Engineering, 2025)
The objective of this review paper is to provide a comprehensive and systematic analysis of the various aspects of vibration-assisted welding (VAW), focusing on its applications, limitations, future potential, and critical evaluations. This review examines welding processes where vibrations serve as a primary mechanism driving the process. It also explores cases where vibrations act as an auxiliary method to enhance operational efficiency and weld quality. A detailed examination is conducted on the physical mechanisms underlying VAW, along with state-of-the-art developments, experimental studies, technological advancements, and diverse applications across relevant fields such as aerospace, automotive, shipbuilding, and biomedical industries. The analysis highlights the benefits of VAW over conventional welding techniques, including enhanced mechanical properties, refined microstructures, and improved overall weld quality. Given these advantages, vibrations have emerged as a transformative technology in welding, leading to notable advancements in productivity and product performance in the twenty-first century. This paper aims to assess the current state of VAW and outline prospective directions for future research and industrial adoption. Further research is needed to standardize VAW methodologies and optimize process parameters for industrial use.